Graphene powder, graphene dispersion, composition, and formed article

JP2025027986APending Publication Date: 2025-02-28TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024111371
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-17
Filing Date
2024-07-11
Publication Date
2025-02-28

AI Technical Summary

Benefits of technology

【0009】 本発明のグラフェン粉末は再分散性が高く、耐腐食性などのバリア性や熱伝導性に優れる組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025027986000001
    Figure 2025027986000001
  • Figure 2025027986000002
    Figure 2025027986000002
Patent Text Reader

Abstract

To provide a graphene powder having excellent dispersibility and a composition having excellent barrier property or thermal conductivity.SOLUTION: The graphene powder consists of particles containing metal and / or metal compounds with a diameter of 50 nm or more and 1000 nm or less attached to a graphene surface.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to graphene powder, and a dispersion, a composition, and a formed product using the same. [Background technology]

[0002] Graphene powder is a two-dimensional crystal made of carbon atoms, and since its discovery in 2004, it has been a material that has attracted much attention. The thin sheet structure of graphene powder has functions such as barrier properties, thermal conductivity, and electrical conductivity. For example, the barrier properties can suppress the permeation of oxygen and water, which are substances that cause metal corrosion. One example of an application that utilizes the functions of graphene powder is corrosion-resistant paint, and it is expected that the use of graphene powder will further improve corrosion resistance.

[0003] In order to utilize graphene powder industrially, a graphene powder dispersion having low electrical resistance and excellent coatability and dispersibility is used. For example, the graphene powder dispersion is a dispersion in which graphene powder is dispersed in a solvent containing 50 mass % or more of N-methylpyrrolidone, and the graphene powder is diluted with N-methylpyrrolidone to a graphene weight fraction of 0.000013, and the graphene powder dispersion has a weight absorption coefficient of 25000 cm at a wavelength of 270 nm. -1 More than 200000cm -1 The following graphene dispersion (see, for example, Patent Document 1) has been proposed. In addition, as a method for producing a graphene dispersion, for example, a production method for producing a graphene dispersion having a reduction step, a micronization step, an organic solvent mixing step, a strong stirring step, and a water removal step (see, for example, Patent Document 2) has been proposed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 047521 [Patent Document 2] International Publication No. 2017 / 047523 Summary of the Invention [Problem to be solved by the invention]

[0005] In order to expand the range of applications of graphene powder, a technique for forming graphene powder into various shapes is required, and for this purpose, it is effective to prepare a dispersion in which graphene powder is dispersed in a thin layer state of a single layer or multiple layers. However, in a dispersion, thin-layer graphene is likely to be stacked and aggregated, and the aggregated sheet-like graphene tends to be easily entangled with each other. For the techniques described in Patent Document 1 and Patent Document 2, further improvement in dispersibility in various compositions is required.

[0006] In some cases, graphene is dried and powdered and then redispersed in a resin or a solvent. In this case, when graphene is powdered by drying or the like, strong layered aggregation occurs, making it very difficult to redisperse, and the dispersibility of graphene is reduced, making it difficult to achieve the desired effect. Therefore, there is a demand for graphene powder that has excellent redispersibility after being dried and powdered.

[0007] Therefore, an object of the present invention is to provide a composition that can give a graphene powder with excellent redispersibility, and a cured product with excellent barrier properties or thermal conductivity. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides graphene powder having particles containing a metal and / or a metal compound and having a particle size of 50 nm or more and 1000 nm or less attached to a surface of graphene. Effect of the Invention

[0009] The graphene powder of the present invention has high redispersibility, and can provide a composition having excellent barrier properties such as corrosion resistance and thermal conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Graphene powder> The graphene powder of the present invention has particles containing a metal and / or a metal compound and having a particle size of 50 nm or more and 1000 nm or less attached to the graphene surface. In the present invention, attention is focused on the particle size of the particles containing a metal and / or a metal compound attached to the graphene surface as an index that affects the redispersibility of the graphene powder.

[0011] The redispersibility of the graphene powder in the present invention is influenced by the particle size of the particles containing a metal and / or a metal compound attached to the graphene surface. By attaching the particles containing a metal and / or a metal compound to the graphene surface, the graphene powder exfoliated into thin layers forms a network and inhibits layering and aggregation. By inhibiting such layering and aggregation, not only the dispersibility in the graphene dispersion is improved, but also the redispersibility of the graphene after the graphene is dried and powdered is improved. When the particle size of the particles containing a metal and / or a metal compound attached to the graphene surface is less than 50 nm, the network between the graphene powders strengthens the layering and aggregation, the redispersibility of the graphene powder is low, the coatability of the graphene dispersion is reduced, and the coating resistance is high. It is preferably 100 nm or more, and more preferably 150 nm or more. When the particle size of the particles containing a metal and / or a metal compound attached to the graphene surface is greater than 1000 nm, the particle size of the particles containing a metal and / or a metal compound becomes large relative to the size of the graphene powder in the planar direction, which inhibits the redispersibility of the graphene powder. The particle size of the particles containing a metal and / or a metal compound of the present invention can be measured by the method described in Measurement Example 1 below.

[0012] The particles containing a metal and / or a metal compound attached to the graphene surface of the present invention can be attached by mixing graphene oxide or reduced graphene with particles containing a metal and / or a metal compound in any step in the graphene powder manufacturing method described later. From the viewpoint of easily controlling the attachment state of the particles containing a metal and / or a metal compound, it is preferable to mix graphene oxide with particles containing a metal and / or a metal compound in the reduction step in the graphene powder manufacturing method described later. A part of the metal and / or metal compound dissolves in a solvent and precipitates and attaches to the graphene surface obtained by reducing graphene oxide as particles containing a simple metal and / or a metal compound. The method based on such a principle has the feature that the size of the particles to be attached, the attachment amount, and the ratio of the attached area can be easily controlled compared to a method of directly mixing a metal and / or a metal compound and attaching it to graphene or a method of precipitating particles on the graphene surface by a hydrothermal reduction method.

[0013] The amount of particles containing a metal and / or a metal compound attached to the graphene surface of the present invention and the ratio of the area of ​​the particles attached to the graphene surface can be changed depending on the size of the particles containing the metal and / or metal compound to be mixed.

[0014] The particles containing the metal and / or metal compound of the present invention include, for example, pigments generally used for paints. When the composition of the present invention is used as a protective paint, the corrosion resistance of the cured product can be improved by selecting a material with a high sacrificial anticorrosive effect depending on the relationship with the object to be protected. For example, when used in a protective paint for steel, the corrosion resistance and durability of the cured product can be improved by selecting zinc particles as the particles containing the metal and / or metal compound due to the sacrificial anticorrosive effect.

[0015] The particles containing a metal and / or a metal compound of the present invention preferably contain scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, and zinc, which are first transition elements. Two or more of these may be contained. It is more preferable to contain zinc, cobalt, and iron. Among these, zinc particles have a high sacrificial anticorrosion effect and can further improve the corrosion resistance of the cured product. In addition, zinc and iron have the effect of reducing graphene oxide, and precipitation of metal compounds occurs on the graphene particle surface accompanied by an oxidation-reduction reaction, so that the reduction reaction and the attachment of particles containing a metal and / or a metal compound can be performed simultaneously, which is preferable.

[0016] In the present invention, the particles containing a metal and / or a metal compound may have, for example, a spherical, flake, thin plate, fibrous, or irregular shape.

[0017] The amount of the particles containing the metal and / or metal compound of the present invention attached is preferably 1% by weight or more and 300% by weight or less with respect to the graphene. The particles containing the metal and / or metal compound attached to the graphene surface form a network with the graphene powder exfoliated into thin layers, suppressing stacking and aggregation. If the amount of the particles containing the metal and / or metal compound attached to the graphene surface is less than 1% by weight with respect to the graphene, stacking and aggregation may be strong due to the network between the graphene powders, and the redispersibility of the graphene powder may be low, and the coating property of the graphene dispersion may be reduced, and the coating resistance may be high. It is preferably 20% by weight or more, and more preferably 40% by weight or more. If the amount of the particles containing the metal and / or metal compound attached to the graphene surface is more than 300% by weight with respect to the graphene, the particles containing the metal and / or metal compound may excessively adhere to the graphene surface, inhibiting the redispersibility of the graphene powder. It is preferably 250% by weight or less, and more preferably 150% by weight or less. The amount of the particles containing the metal and / or metal compound of the present invention attached can be measured by the method described in Measurement Example 2 described later.

[0018] The ratio of the area of ​​the graphene surface to which the particles containing the metal and / or metal compound of the present invention are attached is preferably 1% or more and 70% or less. By attaching the particles containing the metal and / or metal compound to the graphene surface, the graphene powders exfoliated into thin layers form a network and are inhibited from stacking and agglomerating. When the graphene surface coverage of the particles containing the metal and / or metal compound is less than 1%, the graphene powders are strongly stacked and agglomerated due to the network, and the graphene powder tends to have low redispersibility, low coatability when a graphene dispersion is prepared, and high coating resistance. The graphene surface coverage is preferably 10% or more. When the graphene surface coverage of the particles containing the metal and / or metal compound is more than 70%, the particles containing the metal and / or metal compound may excessively adhere to the graphene surface, inhibiting the redispersibility of the graphene powder. The graphene surface coverage is preferably 50% or less. The graphene surface coverage to which the particles containing the metal and / or metal compound of the present invention are attached can be measured by the method described in Measurement Example 3 described later.

[0019] The thickness of one layer of the graphene powder of the present invention is preferably 0.3 nm or more and 10 nm or less. The theoretical minimum value of the thickness of one layer of the graphene powder is 0.3 nm, which indicates that it is a single layer of graphene. On the other hand, by making the thickness of one layer of the graphene powder 10 nm or less, it is possible to prevent the graphene powder from being thickly stacked and aggregated, which leads to a decrease in redispersibility. 8 nm or less is more preferable, and 7 nm or less is even more preferable. The thickness of one layer of the graphene powder of the present invention can be measured by the method described in Measurement Example 4 described later.

[0020] The graphene powder of the present invention preferably has a nitrogen-containing compound on the surface. The nitrogen atom imparts a positive charge to the compound, and can be electrostatically adsorbed to the negative charge of graphene. The nitrogen-containing compound increases the affinity of the graphene surface with the solvent, thereby contributing to increasing dispersibility in the dispersion liquid.

[0021] The nitrogen atom is preferably derived from a primary amine, a secondary amine, a tertiary amine, a quaternary ammonium salt, or a nitrogen-containing cyclic compound. Two or more kinds of nitrogen atoms derived from these may be included, or two or more nitrogen atoms derived from each of these may be included.

[0022] The nitrogen-containing compound may be a low molecular weight compound or a high molecular weight compound. From the viewpoint of further improving corrosion resistance, a low molecular weight compound is preferable, and from the viewpoint of further improving durability, a high molecular weight compound is preferable. Here, a low molecular weight compound refers to a compound having a molecular weight of less than 1000, and a high molecular weight compound refers to a compound having a molecular weight of 1000 or more. Two or more kinds of nitrogen-containing compounds may be used.

[0023] When the nitrogen-containing compound has a low molecular weight, an aromatic compound is preferably used to facilitate attachment of the nitrogen-containing compound to graphene. Examples of aromatic compounds include 2-halogenated anilines, 3-halogenated anilines, 4-halogenated anilines, benzylamine, phenylethylamine, 1-naphthylamine, 2-naphthylamine, aniline, p-toluidine, m-toluidine, o-toluidine, 1-aminoanthracene, 2-aminoanthracene, 9-aminoanthracene, 1-aminopyrene, N-methylaniline, N-ethylaniline, N-isopropylaniline, 4-ethylaniline, 4-isopropylaniline, N,N-dimethylaniline, 4-nitroaniline, diphenylamine, N-methyldiphenylamine, 2,4,6-trimethylaniline, 4-methoxyaniline, N-methylbenzylamine, N,N-dimethylbenzylamine, N,N-diethylbenzylamine, benzamide, dopamine, phenylalanine, tyrosine, tryptophan, histidine, and salts thereof.

[0024] Further examples include polyamines such as 1,6-diaminopyrene, 1,8-diaminopyrene, 1,4-phenylenediamine, 1,3-phenylenediamine, 1,2-phenylenediamine, 1,4-diaminoanthraquinone, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,3-diaminonaphthalene, p-xylylenediamine, m-xylylenediamine, and 1,2,4-triaminobenzene.

[0025] Linear or branched polyetheramines are also preferably used, and are preferably liquid or waxy at room temperature by themselves. From the viewpoint of improving dispersibility, corrosion resistance, and adhesion, the polyetheramine preferably has one or more amino groups, and more preferably has two or more amino groups.

[0026] The weight-average molecular weight of the polyetheramine is preferably 140 or more and 10000 or less. When the weight-average molecular weight is 140 or more, the adhesion to the graphene powder surface is excellent, and it is more preferably 200 or more, and further preferably 500 or more. When the weight-average molecular weight is 10000 or less, there is little concern about clumping due to excessive adhesion, and it is more preferably 8000 or less, and further preferably 6000 or less.

[0027] The polyetheramine preferably contains a polyoxyethylene and / or polyoxypropylene structure. These structures facilitate the generation of a surfactant action and enhance the affinity of the graphene with the solvent or resin. Examples of commercially available products containing such structures include polyethylene glycols #200, #300, #400, #600, #1000, #2000, "UNIOX" (registered trademark) M-400, M-550, M-1000, "UNIOL" (registered trademark) D-200, D-250, D-400G, D-700, D-1000, D-1200, D-2000, D-4000, and the like, all manufactured by NOF Corporation.

[0028] The graphene powder of the present invention preferably has an elemental ratio of oxygen to carbon (O / C ratio) measured by X-ray photoelectron spectroscopy of 0.05 or more and 0.60 or less. The O / C ratio represents the amount of functional groups on the graphene powder and is an index of dispersibility and graphene functionality. From the viewpoint of further improving dispersibility in the dispersion liquid, the O / C ratio is more preferably 0.08 or more. In addition, from the viewpoint of further improving the functionality of graphene such as electrical conductivity, barrier property, and thermal conductivity, the O / C ratio is more preferably 0.30 or less, and even more preferably 0.25 or less.

[0029] The O / C ratio of the graphene powder of the present invention can be measured by the method described in the later-described Measurement Example 5. The O / C ratio of the graphene powder can be easily adjusted to the above-mentioned range, for example, by adjusting the oxidation degree of graphene oxide, which is a raw material, or the reduction degree by the reduction reaction conditions.

[0030] The atomic ratio of nitrogen to carbon (N / C ratio) of the graphene powder of the present invention measured by X-ray photoelectron spectroscopy is an index of the amount of nitrogen attached to the nitrogen-containing compound. The nitrogen-containing compound attached to the graphene can improve the redispersibility of the graphene powder in a solvent and the dispersibility in a dispersion, thereby improving the coatability. The N / C ratio of the graphene powder is preferably 0.005 or more, more preferably 0.007 or more, and even more preferably 0.010 or more. On the other hand, the N / C ratio of the graphene powder is preferably 0.200 or less, more preferably 0.100 or less, and even more preferably 0.050 or less, from the viewpoint of suppressing unintended aggregation.

[0031] The N / C ratio of the graphene powder of the present invention can be measured by the method described in the later-described Measurement Example 6. The N / C ratio of the graphene powder can be easily adjusted to the above-mentioned range, for example, by the amount of the attached nitrogen-containing compound.

[0032] <Graphene dispersion> The graphene powder of the present invention can be made into a graphene dispersion liquid using an organic solvent. The organic solvent is preferably one capable of dissolving the curable resin and / or its precursor described below and capable of volatilization, and can be appropriately selected according to the coating properties of the composition. Specifically, it is preferable to contain at least one selected from the group consisting of mineral oil, methyl isobutyl ketone, methyl ethyl ketone, acetone, butyl acetate, ethyl acetate, aromatic hydrocarbon solvents, and alcohol solvents. Examples of aromatic hydrocarbon solvents include xylene, toluene, ethylbenzene, mesitylene, cumene, tetramethylbenzene, n-hexylbenzene, cyclohexylbenzene, anisole, phenylcyclohexane, and halogenated benzene, and examples of alcohol solvents include hexanol, pentanol, n-butanol, isobutanol, isopropyl alcohol, ethanol, and methanol. Two or more of these may be contained.

[0033] In the present invention, the absorbance was measured when the graphene concentration was adjusted to 0.0065% by weight as an index of the dispersibility of graphene.

[0034] The absorbance of graphene varies depending on the exfoliation state and aggregation state of graphene. Single-layer graphene without aggregation has the highest absorbance, and the absorbance decreases with an increase in the number of layers and the formation of aggregation. When the absorbance at a wavelength of 500 nm is small, the degree of exfoliation of graphene is low, and most of the graphene is in a state of stacked aggregation. The absorbance of graphene at a wavelength of 500 nm is preferably 1.0 or more, more preferably 1.4 or more, and even more preferably 1.6 or more. On the other hand, from the viewpoint of suppressing aggregation due to overdispersion of the graphene dispersion and improving dispersibility in the solvent, the absorbance of graphene at a wavelength of 500 nm is preferably 2.5 or less.

[0035] The absorbance of the graphene dispersion can be measured by the method described in Measurement Example 7 below. In addition, examples of means for adjusting the absorbance of the graphene dispersion to fall within the above-mentioned range include adjusting each of the conditions described in the above-mentioned graphene powder section and obtaining the graphene dispersion by the below-mentioned production method.

[0036] <Curable resin and / or its precursor> A composition containing a curable resin and / or its precursor is preferably used together with the graphene dispersion of the present invention. The curable resin refers to a resin that is cured by volatilization or reaction of a solvent, and examples thereof include epoxy resin, urethane resin, acrylic resin, polyester resin, melamine resin, silicone resin, and alkyd resin. Commercially available curable resins for coating compositions can be suitably used. Two or more of these may be contained. Among these, epoxy resin, urethane resin, and acrylic resin are preferred from the viewpoints of coatability and handling.

[0037] Examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, novolac type epoxy resins, and modified versions of these resins, such as acrylic modified epoxy resins and urethane modified epoxy resins. Two or more of these resins may be included. Among these, bisphenol A type epoxy resins, bisphenol F type epoxy resins, and novolac type epoxy resins are preferred.

[0038] The epoxy equivalent of the epoxy resin is preferably 100 or more and 5000 or less. If the epoxy equivalent is 100 or more, the strength of the coating film obtained from the composition can be improved. On the other hand, if the epoxy equivalent is 5000 or less, the composition can be cured efficiently.

[0039] When the curable resin contains an epoxy resin, it is preferable to further contain an epoxy resin curing agent. Examples of the epoxy resin curing agent include polyfunctional amine compounds and polyamidoamine compounds, and commercially available epoxy resin curing agents can be used. Two or more of these may be contained. The active hydrogen equivalent of the epoxy resin curing agent is preferably 30 or more and 5000 or less. If the active hydrogen equivalent is 30 or more, the strength of the coating film obtained from the composition can be improved. On the other hand, if the active hydrogen equivalent is 5000 or less, the composition can be cured efficiently.

[0040] <Composition> The composition may further contain a solvent and / or any additives. The solvent is preferably one that can dissolve the curable resin and / or its precursor and is volatilizable, and can be appropriately selected depending on the coatability of the composition.

[0041] The graphene content in the composition of the present invention is preferably 0.01% by weight or more and 5.0% by weight or less in the total solid content of the composition. By making the graphene content 0.01% by weight or more, the shielding effect of graphene and the formation of a conductive network can be further improved in corrosion resistance and durability. The graphene content is more preferably 0.1% by weight or more, and even more preferably 0.3% by weight or more in the solid content of the composition. On the other hand, by making the graphene content 5.0% by weight or less, unintended aggregation can be suppressed, and corrosion resistance and durability can be further improved. The graphene content is more preferably 2.5% by weight or less, and even more preferably 1.0% by weight or less in the solid content of the composition.

[0042] <Formation> The formed product containing the graphene powder of the present invention is preferably used as a formed product having a barrier property such as an anti-rust paint, or a formed product having a thermal conductivity such as a heat dissipation material. As one example, a formed product can be obtained by forming a composition containing a graphene dispersion in which the graphene powder of the present invention is dispersed in an organic solvent into a film on a substrate such as a sheet, film, or metal plate.

[0043] <Graphene manufacturing method> The graphene powder of the present invention can be produced, for example, by mixing graphene oxide and a nitrogen-containing compound in a solvent, adding particles containing a metal and / or a metal compound, and then performing a reduction treatment.

[0044] [Graphene oxide] Examples of the method for producing graphene oxide include the Hummers method. Alternatively, commercially available graphene oxide may be purchased. The following is an example of a method for producing graphene oxide using the Hummers method.

[0045] In an ice bath, graphite (graphite powder) and sodium nitrate are added to concentrated sulfuric acid and stirred, and potassium permanganate is gradually added so as not to raise the temperature. The mixture is stirred for 0.2 to 5 hours while maintaining the temperature in the range of 25 to 50°C. Ion-exchanged water is then added to dilute the mixture into a suspension, which is stirred for 5 to 50 minutes at a temperature range of 80 to 100°C. Hydrogen peroxide and ion-exchanged water are then added and stirred for 1 to 30 minutes to obtain a graphene oxide aqueous dispersion. The obtained graphene oxide aqueous dispersion is filtered and washed to obtain a graphene oxide wet cake.

[0046] As the graphite, natural graphite is preferred, and the mesh number is preferably 5000 or less. For 10 g of natural graphite, the amount of sodium nitrate added is preferably 2 to 8 g, the amount of concentrated sulfuric acid added is preferably 150 to 300 ml, the amount of potassium permanganate added is preferably 10 to 40 g, and the amount of hydrogen peroxide added is preferably 40 to 80 g, and the amount of ion-exchanged water added is preferably 10 to 20 times the amount of hydrogen peroxide added. The oxidation degree of graphene oxide can be adjusted to a desired range, for example, by the amount of sodium nitrate or potassium permanganate added as an oxidizing agent. Specifically, the ratio of the amount of sodium nitrate added to graphite (sodium nitrate / graphite) is preferably 0.200 or more and 0.800 or less, and the ratio of the amount of potassium permanganate added to graphite (potassium permanganate / graphite) is preferably 1.0 or more and 4.0 or less.

[0047] [Surface treatment process] Next, the graphene oxide and the nitrogen-containing compound are mixed, and the nitrogen-containing compound is attached to the graphene oxide as a surface treatment agent. In order to mix the graphene oxide and the nitrogen-containing compound well, it is preferable to mix the graphene oxide and the nitrogen-containing compound in a state where both are dispersed in a solvent. At this time, it is preferable that both the graphene oxide and the nitrogen-containing compound are completely dissolved, but it is also possible that a part of them is not dissolved and is dispersed as a solid. As a mixing method, a dispersing machine employing a disperser stirring type, a rotor / stator type, etc. Examples of such dispersing machines include "LABO-LUTION" (registered trademark) Homo Disper 2.5 type (Primix Corporation), Disperser PH91 (SMT Corporation), and "Silverson Mixer" (registered trademark) L5M-A (Silverson Nippon Corporation).

[0048] [Reduction process] Next, particles containing a metal and / or a metal compound are mixed in the solvent to reduce the graphene oxide. A preferred reduction method is chemical reduction. In the case of chemical reduction, examples of the reducing agent include organic reducing agents and inorganic reducing agents. Among these, metals and / or metal compounds having an oxidation-reduction effect are preferred, and zinc, cobalt, iron, and the like are more preferred. An inorganic reducing agent such as sodium dithionite or potassium dithionite may be used in combination. In the case of metals and / or metal compounds having no oxidation-reduction activity, sodium dithionite, potassium dithionite, etc. are preferably used as inorganic reducing agents.

[0049] [Filtration and concentration process] Next, the graphene dispersion obtained in the reduction step is filtered and concentrated. The filtration and concentration step is a step of removing a part of the solvent of the reduced graphene dispersion by suction filtration. As the suction filtration, reduced pressure suction filtration is preferable from the viewpoint of suppressing stacking of graphene. Moreover, the operation of redispersing the obtained graphene dispersion in a solvent and filtration and concentration may be repeated multiple times. In the present invention, it is preferable to perform the filtration and concentration step two or more times and six or less times.

[0050] [Drying process] Next, the graphene dispersion obtained in the filtration and concentration step is dried. The drying step is a step of removing the solvent remaining in the filtration and concentration step to powderize the graphene dispersion. Examples of the drying method include hot air drying and vacuum drying, but freeze drying is preferred from the viewpoint of suppressing stacking of the graphene powder.

[0051] <Method of manufacturing graphene dispersion> The graphene dispersion of the present invention can be prepared, for example, by redispersing graphene powder in a solvent.

[0052] [Dispersion process] The graphene powder obtained in the drying step is redispersed in an organic solvent. In the present invention, the graphene dispersion that has been subjected to the dispersion step is preferably filtered and concentrated again, in order to eliminate stacks of graphene particles and to further improve the redispersibility of the graphene powder in the solvent and the dispersibility in the dispersion.

[0053] In the dispersion step, the slurry obtained by mixing the graphene powder with the organic solvent is preferably stirred with a dispersing machine using a dispersing stirrer, a rotor / stator type, or the like. The higher the peripheral speed when stirring the slurry, the more efficiently the stacked graphene can be peeled off by shear force, and stacks can be eliminated, and the redispersibility of the graphene powder in the solvent and the dispersibility in the dispersion can be further improved. The solid content concentration of the graphene dispersion obtained in the dispersion step can be measured by the method described in Measurement Example 8 below.

[0054] <Method of producing the composition> Next, an example of a method for producing a composition using a graphene dispersion will be described. For example, a method of mixing a graphene dispersion with a curable resin and / or its precursor, inorganic particles, and, if necessary, a solvent or any additives, or a method of mixing graphene with a commercially available coating composition containing inorganic particles, a curable resin and / or its precursor, etc., can be mentioned. In the former method, the inorganic particles and the graphene dispersion can be added and mixed simultaneously, or can be added and mixed separately. From the viewpoint of further enhancing the dispersibility of graphene, it is preferable to mix graphene and inorganic particles with a solution in which a curable resin and / or its precursor is dissolved in a solvent.

[0055] Examples of the mixing device include mixers and kneaders such as a bead mill, a homodisper, a homomixer, a planetary mixer, and a sand mill.

[0056] When the composition of the present invention contains a curable resin precursor, the base agent (e.g., epoxy resin) and the curing agent (e.g., epoxy resin curing agent) may be stored in separate containers until immediately before use. In this case, the graphene and inorganic particles may be contained in the base agent or the curing agent.

[0057] Examples of inorganic particles include extender pigments that are generally used for paints. When the composition of the present invention is used as a protective paint, the corrosion resistance of the cured product can be improved by selecting a material with a high sacrificial anticorrosive effect according to the relationship with the object to be protected. For example, when used as a protective paint for steel, the corrosion resistance and durability of the cured product can be improved by selecting zinc particles as the inorganic material due to the sacrificial anticorrosive effect.

[0058] The inorganic particles preferably contain zinc, iron oxide, mica, talc, bentonite, silicon dioxide, titanium oxide, aluminum oxide, barium sulfate, stainless steel, glass, or aluminum. Two or more of these may be contained.

[0059] Examples of the shape of the inorganic particles include spherical, flake, thin plate, fibrous, and amorphous.

[0060] Among these, mica, talc, bentonite, flaky titanium oxide, stainless steel flakes, glass flakes, and aluminum flakes have a high shielding effect due to their flat shape, and can further improve the corrosion resistance of the cured product. In addition, zinc particles have a high sacrificial anticorrosive effect, and can further improve the corrosion resistance of the cured product. It is preferable to combine zinc particles with talc, bentonite, glass flakes, etc., and the viscosity of the composition and the mechanical properties of the coating film obtained from the composition can be easily adjusted to a desired range.

[0061] The average particle size of the inorganic particles is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less, from the viewpoint of suppressing defects such as pinholes and further improving the corrosion resistance of the cured product. On the other hand, from the viewpoint of enhancing the shielding effect and sacrificial anticorrosion effect of the inorganic particles and further improving the corrosion resistance and durability of the cured product, it is preferably 1.0 μm or more, more preferably 3.0 μm or more, and even more preferably 5.0 μm or more. The average particle size of the inorganic particles can be easily adjusted to the above range using known particle crushing techniques. In addition, commercially available inorganic particles having a desired particle size can be purchased and used.

[0062] The formed product of the present invention includes the graphene powder of the present invention, and refers to a product obtained by forming the composition of the present invention into a desired shape on a substrate or the like. For example, it is a coating film or a cast body before and after drying. Specific examples thereof are shown below.

[0063] The composition containing the graphene dispersion of the present invention can be used as a composite material imparted with the functions of graphene, such as barrier property, thermal conductivity, electrical conductivity, etc., by forming the composition into a film shape on a metal substrate, and then drying or curing the composition through a reaction.

[0064] In the present invention, the term "material having a barrier property" refers to, for example, a coating material such as a paint having corrosion resistance, a material suppressing permeation of a substance that suppresses the permeation of gas, etc. Furthermore, the term "material having a thermal conductivity" refers to, for example, a thermal diffusive material, a heat dissipating material, a heat reflecting material, a heat generating material, etc.

[0065] The graphene of the present invention has excellent mixability and bonding in resin, and therefore the effect is easily obtained, particularly when used in the form of a coating or film. When a coating or film is formed, stress is applied to the interface between the graphene and the resin due to the influence of shrinkage and the like accompanying the curing of the resin, which may easily cause defects. However, by using the graphene of the present invention, the bonding between the graphene and the resin is enhanced, and the occurrence of defects can be suppressed. Furthermore, since the graphene of the present invention has excellent dispersibility and mixability, the graphene is uniformly distributed, and the functionality of the graphene can be efficiently exhibited.

[0066] Therefore, the composition containing the graphene dispersion of the present invention can be suitably used as, for example, a coating film, an electrode, or a thermal conductor. Examples of the coating film include corrosion-resistant paint, waterproof paint, gas barrier film, and impact-resistant film. Examples of the electrode include electrodes for batteries and electrodes for sensors. Examples of the thermal conductor include heat dissipation materials for electronic devices, heat-dissipating coating materials for pipes, and cooling and antifreezing materials for buildings.

[0067] Examples of the metal substrate include metal-deposited films for gas barriers, electrode substrates such as aluminum foil and copper foil, metal housings and members for various electronic components, steel housings and structures (vehicles such as automobiles and ships, buildings such as bridges and iron bridges, factory equipment, etc.).

[0068] The composition of the present invention can be suitably used as a coating film formed by coating on a substrate and drying. Examples of the coating method include applicator coating, bar coating, spin coating, roller coating, brush coating, spray coating, etc. The drying method can be appropriately selected depending on the solvent, resin, and application, and examples of the drying method include natural drying, heat drying, and hot air drying.

[0069] The composition of the present invention may be used, for example, by injecting it into a crack and curing it by drying and / or a crosslinking reaction. As the injection and curing method, a known method can be used.

[0070] The composition of the present invention formed into a film on a substrate has excellent barrier properties such as corrosion resistance and durability. As an index of barrier properties, it is preferable that the water vapor transmission rate and oxygen transmission rate are low. Specifically, the water vapor transmission rate measured by the method described in Measurement Example 11 below is 300 g / m 2 24h or less is preferable, 250g / m 2 24h or less is preferable, 225g / m 2 24 hours or less is even more preferable. Water acts as an oxygen carrier, so the lower the water vapor permeability, the lower the oxygen permeability tends to be.

[0071] As another indicator of the barrier property, a corrosion potential, which indicates the resistance to corrosion, is preferably low. Specifically, the corrosion potential measured by the method described in Measurement Example 12 below is preferably −0.9 V or less, and more preferably −1.0 V or less.

[0072] As an index of barrier properties, it is preferable that the time to reach score 3 (width of red rust at the notch is 2 mm) is longer when a salt spray resistance test is performed by the method described in Measurement Example 13 described later. The time to reach score 3 in the salt spray resistance test is significantly extended in the presence of the sacrificial corrosion protection effect of zinc. For this reason, when the composition does not contain zinc, the time to reach score 3 in the salt spray resistance test is preferably 500 hours or more, more preferably 600 hours or more, and even more preferably 700 hours or more. On the other hand, when the composition contains zinc, the time to reach score 3 in the salt spray resistance test is preferably 2000 hours or more, and more preferably 2500 hours or more. EXAMPLES

[0073] The present invention will be described below with reference to examples. First, the evaluation methods used in the examples and comparative examples will be described.

[0074] [Measurement Example 1: Particle size (nm) of particles containing metals and / or metal compounds] The particle size of the particles containing metals and / or metal compounds attached to the graphene powder surface produced in each Example and Comparative Example was measured by electron microscope observation. The graphene powder produced in each Example and Comparative Example was diluted to 0.0065% by weight using n-butanol, 1 μL was dropped on aluminum foil, dried, and attached to the aluminum foil. The graphene powder on the aluminum foil was observed at a magnification of 20,000 times using a field emission scanning electron microscope FE-SEM S-5500 (Hitachi High-Tech Corporation), and the longest diameter and shortest diameter of each particle containing metals and / or metal compounds attached to the graphene powder surface were measured for 30 random particles, and the arithmetic average was calculated. This was performed for 30 random graphene powders, and the average was taken as the particle size of the particles containing metals and / or metal compounds attached to the graphene powder surface.

[0075] [Measurement Example 2: Particle adhesion amount (wt%) of particles containing metal and / or metal compound] The amount of particles containing metals and / or metal compounds attached to the graphene powder surface produced in each of the examples and comparative examples was measured by ICP emission spectroscopy. The graphene dispersion obtained in the filtration and concentration step in the graphene manufacturing method described above was redispersed in a solvent, and centrifuged at 5000 rpm using a small centrifuge H-112 (Kokusan Co., Ltd.) to separate graphene and particles containing metals and / or metal compounds, and the graphene on the supernatant side was dried by freeze-drying to obtain graphene powder. 4 to 5 mg of graphene powder was weighed into a platinum crucible, sulfuric acid was added, and the mixture was heated and incinerated using a hot plate and a burner. The obtained incinerated product was dissolved in sodium carbonate, heated and dissolved by adding water, and then nitric acid was added and the mixture was diluted with water to a constant volume. The amount of metals and / or metal compounds attached to the graphene powder surface was measured for this solution by ICP emission spectroscopy, and the amount of metals and / or metal compounds attached to the graphene powder surface was quantified.

[0076] [Measurement Example 3: Particle adhesion coverage (%)] The particle adhesion coverage of particles containing metals and / or metal compounds attached to the graphene powder surface produced in each Example and Comparative Example was calculated by the number of pixels from elemental mapping by SEM-EDX analysis (scanning electron microscope energy dispersive X-ray analysis). The graphene powder produced in each Example and Comparative Example was diluted to 0.0065% by weight using n-butanol, 1 μL was dropped on mica, dried, and attached to the mica. The graphene powder on the mica was observed using a field emission scanning electron microscope FE-SEM S-5500 (Hitachi High-Tech Corporation) by adjusting the magnification so that one graphene particle was included in the entire observation field, and elemental mapping was performed by EDX analysis using EDAX Genesis (Ametech Corporation). The obtained target elemental mapping image was binarized, and the particle adhesion coverage of particles containing metals and / or metal compounds on the graphene surface was calculated from the number of pixels in which a signal derived from the target element was detected relative to the number of pixels in the entire elemental mapping image, and the arithmetic average of the particle adhesion coverage of 10 different graphene particles was obtained.

[0077] [Measurement Example 4: Average thickness of graphene powder (nm)] The graphene powder prepared in each of the examples and comparative examples was diluted to 0.01% by weight with an organic solvent, and treated for 60 seconds at a rotation speed of 40 m / s (shear rate: 20,000 per second) using a "Filmix" (registered trademark) 30-30 type (Primix Corporation). The graphene diluted solution was dropped onto mica, dried, and graphene was attached onto the mica. The graphene on the mica was observed with an atomic force microscope (Dimension Icon; Bruker Corporation) in an enlarged field of view of about 1 to 10 μm square, and the thickness of each of 10 randomly selected graphenes was measured. The thickness of each graphene was calculated as the arithmetic average of the thickness measurements at five randomly selected points on each graphene, and the average thickness of one layer of the graphene powder was calculated by calculating the arithmetic average of the thicknesses of the 10 graphenes.

[0078] [Measurement Example 5: Measurement of O / C ratio by X-ray photoelectron spectroscopy] The graphene powders produced in each of the examples and comparative examples were subjected to photoelectron spectroscopy using an X-ray photoelectron spectrometer Quantera SXM (ULVAC-PHI, Inc.). The excitation X-ray was monochromatic AlK α1,2 The X-ray diameter was 200 μm, and the photoelectron escape angle was 45°. The main C1s peak due to carbon atoms was assigned to 284.3 eV, and the O1s peak due to oxygen atoms was assigned to a peak near 533 eV. O / C was calculated from the area ratio of the O1s peak and the C1s peak, and the obtained value was rounded off to two decimal places.

[0079] [Measurement Example 6: Measurement of N / C ratio by X-ray photoelectron spectroscopy] The graphene powders produced in each of the examples and comparative examples were subjected to photoelectron spectroscopy using an X-ray photoelectron spectrometer Quantera SXM (ULVAC-PHI, Inc.). α1,2The X-ray diameter was 200 μm, and the photoelectron escape angle was 45°. The main C1s peak due to carbon atoms was assigned to 284.3 eV, and the N1s peak due to nitrogen atoms was assigned to a peak near 402 eV. N / C was calculated from the area ratio of the N1s peak and the C1s peak, and the value was rounded off to the fourth decimal place to obtain the third decimal place.

[0080] [Measurement Example 7: Absorbance] The absorbance of the graphene dispersions prepared in each of the Examples and Comparative Examples was measured using a "UV7" (registered trademark) spectrophotometer (Mettler Toledo). A quartz cell with an optical path length of 10 mm was used. The organic solvent used in each of the Examples and Comparative Examples was added to the graphene dispersions prepared in each of the Examples and Comparative Examples so that the graphene concentration was 0.0065% by weight, and the diluted solution was treated for 10 minutes with an ultrasonic cleaner (ASU-6M, AS ONE Corporation) with an output of 130 W and an oscillation frequency of 40 kHz at high output setting, and the absorbance was measured after a baseline measurement was performed in advance with the organic solvent used for adjusting the concentration.

[0081] [Measurement example 8: Solid content concentration (wt%)] The graphene dispersions prepared in each of the Examples and Comparative Examples were placed on an aluminum cup with a known weight, and the weight was measured. The graphene dispersions were then heated on a hot plate set at 120° C. for 1.5 hours to volatilize the solvent. The solid content concentration of the graphene dispersions was calculated from the weight of the graphene dispersions before heating and the amount of solvent volatilization calculated from the weight difference before and after heating. This was repeated three times to obtain the average value.

[0082] The solid content concentration of the graphene oxide wet cake produced in Synthesis Example 1 was measured in the same manner as in measuring the solid content concentration of the graphene dispersion, except that the temperature was adjusted to 100°C.

[0083] The graphene dispersions prepared in the respective Examples and Comparative Examples contain particles containing a metal and / or a metal compound mixed in the reduction step. When the solid content concentration of only graphene is of interest, it is calculated from the compounding ratio of the particles containing a metal and / or a metal compound mixed in the reduction step.

[0084] [Measurement example 9: Coating film resistance (Ω cm)] The graphene dispersions prepared in each of the Examples and Comparative Examples were applied by the method described in Evaluation Example 1 described later, and then dried in a hot air drying oven at 80° C. for 1 hour, and then dried at 200° C. for 2 hours to remove the solvent, to obtain a dried coating film. The coating film resistance of the graphene in the dried coating film was measured using a low resistivity meter "Loresta-GX" (registered trademark) MCP-T700 (Nitto Seiko Analytech Co., Ltd.).

[0085] [Measurement example 10: Number of defects] The compositions prepared in each of the Examples and Comparative Examples were spray-coated on a PET film of A4 size and 50 μm thick, then dried at room temperature and left to harden for one week to form a 100 μm thick cured film. The surface of the obtained cured film was observed at 100 times magnification using an optical microscope, and 10 randomly selected points were observed for defects such as cracks and pinholes, and the corrosion resistance was evaluated based on the number of points where defects were found. The fewer the points where defects were found, the better the corrosion resistance.

[0086] [Measurement Example 11: Water Vapor Permeability (g / m 2 24h)] In the same manner as in Measurement Example 10, a 100 μm thick cured film was formed on an A4 size 50 μm thick PET film. The cured film was placed face down and the PET film side was pulled up to peel off the cured film. The obtained cured film was cut into 12 cm squares, and the part that touched the packing of the chamber was protected with aluminum tape, and the film was placed in a water vapor transmission rate measuring device PERMATRAN-W 3 / 33MG+ (MOCON). The water vapor transmission rate was measured using the constant pressure method under conditions of a chamber temperature of 20°C and a relative humidity of 90%. The lower the water vapor transmission rate, the better the corrosion resistance.

[0087] [Measurement Example 12: Corrosion Potential (V)] The compositions prepared in each of the examples and comparative examples were applied to a sandblasted general structural rolled steel plate (material: SS400) measuring 15 cm x 7 cm x 0.8 cm thick using a spray gun, dried at room temperature, and left to stand for one day to form a cured film. The thickness of the cured film was adjusted to 80 ± 10 μm. A commercially available rust-preventive paint (Nippon Paint Co., Ltd. "Zinky" (registered trademark) 8000HB) was applied to the exposed parts of the substrate where no cured film was formed using a brush, and the paint was left to stand for one week after drying to cure, to obtain a test plate. The test plate was connected to the working electrode of a potentiostat Model 1480A (Solartron Analytical Co., Ltd.), a platinum electrode to the counter electrode, and a silver-silver chloride electrode to the reference electrode. The test plate was immersed in 300 mL of a 3.5 wt % sodium chloride aqueous solution (pH = 7) at room temperature in a 500 mL beaker, and measurement was started. The measurement was first performed by stabilizing the sample with an open circuit for the initial 900 seconds, and then the voltage was swept from -0.2V to +0.5V at a speed of 0.003V / s in voltage sweep mode, and the current value was measured. The absolute value of the obtained current value was plotted, and the voltage at which the current value was minimized was taken as the corrosion potential. The lower the corrosion potential (the larger the absolute value), the better the corrosion resistance.

[0088] [Measurement example 13: Salt spray resistance time (h)] A test plate was obtained in the same manner as in Measurement Example 12. A linear cut 5 cm long and 0.5 to 1.0 mm deep was made in the center of the test plate, and the plate was set in a salt spray tester (STP-30, Suga Test Instruments Co., Ltd.). After starting the salt spray test using a 5 wt% sodium chloride aqueous solution (pH = 7) heated to 35°C, each sample was scored according to the occurrence of rust as shown below, and the change over time was recorded. Durability was evaluated from the time it took to reach a score of 3. Score 0: Close to the original condition, no red rust observed. When zinc is used, this refers to a condition where white rust is observed due to the sacrificial corrosion protection effect, but no red rust is observed. Score 1: Red rust is visible throughout the cut area. Score 2: Red rust less than 2 mm wide is found throughout the entire cut area, and there is one or more areas around the cut where red rust can be seen due to bulging of the hardened film or pitting corrosion outside the cut area. Score 3: Multiple blisters or pitting are observed around the notch, and the width of the red rust at the notch is 2mm or more.

[0089] [Evaluation example 1: Paste application] The graphene dispersions prepared in each of the Examples and Comparative Examples were applied onto a 130 μm-thick "Kapton" (registered trademark) polyimide film (Toray DuPont Co., Ltd.) using a doctor blade (300 μm), and the coating property, which is an evaluation index of dispersibility, was evaluated on a 5-point scale by visually observing the surface of the applied film. The evaluation criteria were as follows, and a score of 3 or more was determined to be good dispersibility. 5 points: No unevenness or smudges on the coating surface are observed 4 points: Approximately 95% of the coating surface area is free of uneven coating or smudges 3 points: No unevenness or smudges are found on approximately 90% to less than 95% of the coating surface area 2 points: No unevenness or smudges are observed on approximately 80% to less than 90% of the coating surface area 1 point: There is a lot of unevenness or smudges on the coating surface.

[0090] [Synthesis Example 1: Method for producing graphene oxide dispersion] Using 1500 mesh natural graphite powder (Shanghai Yifan Graphite Co., Ltd.) as the raw material, 220 ml of 98% concentrated sulfuric acid, 5 g of sodium nitrate, and 30 g of potassium permanganate were added to 10 g of natural graphite powder in an ice bath, and the mixture was stirred for 1 hour to maintain the temperature of the mixture below 20 ° C. The mixture was removed from the ice bath and stirred in a water bath at 35 ° C. for 4 hours, after which 500 ml of ion-exchanged water was added, and the resulting suspension was stirred at 90 ° C. for another 15 minutes. Finally, 600 ml of ion-exchanged water and 50 ml of hydrogen peroxide were added and stirred for 5 minutes to obtain a graphene oxide dispersion. The obtained graphene oxide dispersion was filtered, metal ions were washed with a dilute hydrochloric acid solution, acid was washed with ion-exchanged water, and washing was repeated until the pH became 7, and the mixture was concentrated by suction filtration to produce a graphene oxide wet cake. The solid content concentration of the produced graphene oxide wet cake, measured by Measurement Example 8, was 45 wt %. 11.1 g of the obtained graphene oxide wet cake (graphene oxide solid content: 5 g) was mixed with 988.9 g of ion-exchanged water and stirred for 30 minutes at 10,000 rpm using a rotor / stator Silverson mixer L5M-A to obtain 1,000 g of graphene oxide dispersion with a graphene oxide concentration of 0.5 wt%.

[0091] [Example 1] (Method of producing graphene powder) Surface treatment agent mixing step: A sodium hydroxide aqueous solution was added to 1,000 g of the graphene oxide dispersion produced in Synthesis Example 1 to adjust the pH to 8.5, and 2.5 g of dopamine hydrochloride was mixed in as a surface treatment agent. The mixture was then stirred for 30 minutes at a rotation speed of 10,000 rpm using a rotor / stator Silverson mixer L5M-A.

[0092] Reduction step: 10.0 g of zinc powder having an average particle size of 10 μm was added to the graphene oxide dispersion after the surface treatment, and the mixture was stirred at a rotation speed of 10,000 rpm for 30 minutes using a rotor / stator Silverson mixer L5M-A to carry out a reduction reaction, thereby obtaining a graphene dispersion.

[0093] Filtration and concentration: The obtained graphene dispersion was filtered using a vacuum suction filter to obtain a graphene dispersion. 100.0 g of the obtained graphene dispersion was mixed with 1000 g of ion-exchanged water, and redispersion was performed by stirring at a rotation speed of 10,000 rpm for 10 minutes using a rotor / stator Silverson mixer L5M-A. A second filtration and concentration process was performed on the obtained graphene redispersion to obtain a graphene dispersion. The solid content concentration of the graphene dispersion measured in Measurement Example 8 was 12.4 wt%, and the solid content concentration focusing only on graphene was 3.0 wt%.

[0094] Drying step: 10 g of the obtained graphene dispersion was mixed with 90 g of ion-exchanged water, and the mixture was stirred for 5 minutes at a rotation speed of 10,000 rpm using a rotor / stator type Silverson mixer L5M-A to perform redispersion. 100 g of the obtained graphene dispersion was placed in a 1000 mL eggplant-shaped flask, frozen with liquid nitrogen so as to thinly adhere to the inner wall of the eggplant-shaped flask, and freeze-dried for 12 hours using an "EYELA" (registered trademark) freeze dryer FDU-1200 (Tokyo Rikakikaisha) at a temperature of -30°C or less and a pressure of 30 Pa or less to obtain graphene powder. This operation was performed multiple times until the required amount of graphene powder was obtained.

[0095] For the obtained graphene powder, the physical properties of the graphene powder were measured by the methods described in Measurement Examples 1 to 6. The results are shown in Table 2.

[0096] (Method of producing graphene dispersion) 12.38 g of the obtained graphene powder and 187.62 g of n-butanol were mixed and stirred for 10 minutes at 10,000 rpm using a rotor / stator Silverson mixer L5M-A to obtain a graphene dispersion. The solids concentration of the obtained graphene dispersion was 6.2 wt%, and the solids concentration focusing only on graphene was 1.5 wt%.

[0097] For the obtained graphene dispersion, physical properties of the graphene dispersion were measured by the methods described in Measurement Examples 7 and 9, and the results were shown in Table 2. In addition, the graphene dispersion was evaluated by the method described in Evaluation Example 1, and the results were shown in Table 2.

[0098] (Method of preparing the composition) 8.2 g of "Epiclon" (registered trademark) 1050 (bisphenol A type epoxy resin, epoxy equivalent 450-500 g / eq) manufactured by DIC Corporation was weighed as an epoxy resin, 18 g of xylene and 2 g of n-butanol were added, and the mixture was heated to 90°C to dissolve it, and then stirred for 20 minutes at 3000 rpm using a Labo-lution Homo Disper 2.5 type. 79.7 g of zinc powder (average particle size 10 μm) manufactured by Hayashi Pure Chemical Industries Co., Ltd. and 7.0 g of the graphene dispersion obtained by the above-mentioned method (graphene content 0.1 wt% relative to the total solid weight in the composition) were added to the obtained solution, and the mixture was stirred for 30 minutes at 3000 rpm using a Labo-lution Homo Disper 2.5 type. 11.7 g of Newmide 515 (product name) manufactured by Harima Chemical Group, Inc. (polyamide amine, active hydrogen equivalent 185, solid content 70% by weight, solid weight 8.2 g) was added as an epoxy resin curing agent, 3.5 g of bentonite was added, and the mixture was further stirred at 3000 rpm for 10 minutes using a Labo-Lusion Homo Disper 2.5 to homogenize the mixture, thereby preparing a composition.

[0099] The obtained compositions were evaluated for corrosion resistance and durability by the methods described in Measurement Examples 10 to 13. The results are shown in Table 2.

[0100] [Example 2] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 2 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0101] [Example 3] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 5 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0102] [Example 4] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 20 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0103] [Example 5] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 30 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0104] [Example 6] A graphene powder and a graphene dispersion were prepared in the same manner as in the preparation of the graphene dispersion in Example 1, except that the organic solvent was changed to xylene. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0105] [Example 7] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the surface treatment agent was changed to phenylethylamine hydrochloride in the surface treatment step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0106] [Example 8] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the surface treatment agent was changed to 1,4-phenylenediamine in the surface treatment step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0107] [Example 9] A graphene powder and a graphene dispersion were prepared in the same manner as in the preparation of the graphene powder in Example 1, except that no surface treatment agent was mixed in the surface treatment step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0108] [Example 10] A graphene oxide dispersion was prepared in the same manner as in Example 1 except that the oxidation degree was changed in Synthesis Example 1, and a graphene powder and a graphene dispersion were prepared. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0109] [Example 11] A graphene oxide dispersion was prepared in the same manner as in Example 1 except that the oxidation degree was changed in Synthesis Example 1, and a graphene powder and a graphene dispersion were prepared. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0110] [Example 12] A composition was prepared in the same manner as in Example 1, except that the amount of graphene dispersion added was changed to 3.5 g (graphene content: 0.05 wt % relative to the total solid weight in the composition) and the amount of zinc powder added was changed to 79.9 g. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0111] [Example 13] A composition was prepared in the same manner as in Example 1, except that the amount of graphene dispersion added was changed to 35.0 g (0.5 wt% graphene content relative to the total solid weight in the composition) and the amount of zinc powder added was changed to 78.1 g. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0112] [Example 14] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 40 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0113] [Example 15] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 50 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0114] [Example 16] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the amount of zinc powder added in the reduction step was changed to 5.0 g. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0115] [Example 17] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the amount of the surface treatment agent added in the surface treatment step was changed to 0.9 g. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0116] [Comparative Example 1] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 80 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0117] [Comparative Example 2] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that the average particle size of the zinc powder was changed to 1 μm in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0118] [Comparative Example 3] A graphene powder and a graphene dispersion were prepared in the same manner as in Example 1, except that zinc powder was replaced with sodium dithionite in the reduction step. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0119] [Comparative Example 4] A graphene powder and a graphene dispersion were prepared in the same manner as in the preparation of the graphene powder in Example 1, except that 1000 g of the graphene oxide dispersion prepared in Synthesis Example 1 was replaced with 1000 g of a graphene dispersion prepared by mixing 5.0 g of graphene nanoplatelet powder with 995.0 g of ion-exchanged water and stirring the mixture at a rotation speed of 10,000 rpm for 30 minutes using a rotor / stator Silverson mixer L5M-A. The obtained graphene powder, graphene dispersion, and composition were evaluated by the above-mentioned methods, and the results are summarized in Table 2.

[0120] [Table 1]

[0121] [Table 2]

Claims

1. Graphene powder having particles containing a metal and / or a metal compound and having a particle size of 50 nm or more and 1000 nm or less attached to a surface of graphene.

2. 2. The graphene powder according to claim 1, wherein the particles containing the metal and / or metal compound are attached to the graphene in an amount of 1% by weight to 300% by weight.

3. The graphene powder according to claim 2 , wherein the particles containing the metal and / or metal compound are attached to an area of ​​1% to 70% of the graphene surface.

4. The graphene powder according to claim 3 , wherein the particles containing the metal and / or metal compound are attached to an area of ​​10% to 50% of the graphene surface.

5. 2. The graphene powder according to claim 1, wherein the metal and / or metal compound comprises at least one selected from zinc, cobalt and iron.

6. The graphene powder according to claim 1, wherein the graphene has an average thickness of 0.3 nm or more and 10 nm or less.

7. The graphene powder according to claim 6 , wherein the graphene powder has a nitrogen-containing compound on a surface thereof.

8. 8. The graphene powder according to claim 7, wherein the graphene powder has an elemental ratio of oxygen to carbon (O / C ratio) of 0.05 or more and 0.60 or less, and an elemental ratio of nitrogen to carbon (N / C ratio) of 0.005 or more and 0.200 or less, as measured by X-ray photoelectron spectroscopy.

9. A graphene dispersion obtained by dispersing the graphene powder according to any one of claims 1 to 8 in an organic solvent.

10. The graphene dispersion according to claim 9 , wherein the organic solvent comprises an aromatic hydrocarbon-based solvent and / or an alcohol-based solvent.

11. A composition comprising the graphene dispersion according to claim 10 and a curable resin and / or a precursor thereof.

12. The composition according to claim 11, wherein the graphene content is 0.01 wt % or more and 5.0 wt % or less based on the total solid content in the composition.

13. A formed article comprising the graphene powder according to any one of claims 1 to 8.

14. 14. The formation of claim 13, which has barrier properties.

15. The formation of claim 13, which is thermally conductive.

Citation Information

Patent Citations

  • Graphene dispersion, process for producing same, process for producing particles of graphene / active material composite, and process for producing electrode paste

    WO2017047521A1

  • Graphene dispersion, process for producing same, process for producing particles of graphene / active material composite, and process for producing electrode paste

    WO2017047523A1